Connecting Cairo to the Nile: Renewing life and heritage on the river - George Mathias Kondolf; Louise Mozingo; Rachael Marzion; Krishnachandran Balakrishnan; Amir Gohar; Linda Jewell; Sami Sabri Shaker; Ahmed Shalaby; Noha Abbassy; Tami Church (University of California, Institute of Urban and Regional Development (IURD), 2011)
As urban waterfronts around the world de-industrialize, cities are increasingly capitalizing on these opportunities to provide open space and alternative commuting routes along riverbanks, bringing residents and visitors back to the waterfronts. Cairo has remarkable opportunities to reconnect its people with the river that was historically its heart. In an intensive workshop involving 23 students and seven faculty from Cairo University (CU), The American University in Cairo (AUC), and the University of California, Berkeley (UCB), interdisciplinary teams systematically inventoried existing conditions along a 12-km reach of the Nile from Maadi to Tahrir Square, recording river-bank relations, building heights and conditions, circulation, and land-use.
Keywords: 330